2005
DOI: 10.1161/01.atv.0000165656.65359.23
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Implications of the Krüppel-Like Family of Transcription Factors

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 52 publications
4
89
0
Order By: Relevance
“…Both proteins are members of the same Kru¨ppel-like/Sp family of zinc finger transcription factors. KLFs regulate differentiation and development through their roles in signal transduction, cell proliferation, apoptosis and angiogenesis (Bieker, 2001;Black et al, 2001;Suzuki et al, 2005). KLF6 is ubiquitously expressed and contains a highly conserved COOH terminus zinc finger DNAbinding domain that interacts with GC box motifs in target promoters, often containing no or only weak TATA-boxes (Turner and Crossley, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins are members of the same Kru¨ppel-like/Sp family of zinc finger transcription factors. KLFs regulate differentiation and development through their roles in signal transduction, cell proliferation, apoptosis and angiogenesis (Bieker, 2001;Black et al, 2001;Suzuki et al, 2005). KLF6 is ubiquitously expressed and contains a highly conserved COOH terminus zinc finger DNAbinding domain that interacts with GC box motifs in target promoters, often containing no or only weak TATA-boxes (Turner and Crossley, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence to suggest that KLFs play a central role in the regulation of cell growth, proliferation, differentiation and tumorigenesis. KLF5 is the fifth member of this family, and has been demonstrated to mediate various aspects of cardiovascular physiology, including remodeling, differentiation and development (Shi et al, 1999;Nagai et al, 2003;Ghaleb et al, 2005;Suzuki et al, 2005). Recent studies also suggest that KLF5 plays a role in tumor progression in breast and prostate cancers (Chen et al, 2002(Chen et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…23b). Finally, we tested whether other KLF family members, including KLF2 and KLF5, may contribute to Twist1-Jagged1-induced endothelial differentiation 17 . However, quantitative real-time PCR analysis showed that knockdown of Jagged1 in Twist1-overexpressing OECM1 cells did not decrease the KLF2 or KLF5 mRNA levels ( Supplementary Fig.…”
Section: Oecm1-twist1mentioning
confidence: 99%
“…KLF4 is a core component of the pluripotency transcription network that has been used to reprogram somatic cells into induced pluripotent stem cells 16 . KLF4 regulates endothelial barrier and is implicated in vasculogenesis 17,18 . Recent evidence has shown that pluripotency factors regulate endoderm specification 19 .…”
mentioning
confidence: 99%